Analysis of the Effect of Equipment Readiness on the Tank Cleaning Process (Case Study of MT. Akra 102) - Iskandar, Iskandar; Santoso, Aris Kurniawan (RSF Conference Series: Engineering and Technology, 2023)
Tank cleaning is defined as the activity of cleaning tanks from residues of previous cargo, including cleaning and checking pumping equipment, heater equipment, filling pipes, ventilation pipes and auxiliary engines. During the tank cleaning process there were many obstacles such as the tool not working normally, the crew’s lack of knowledge, and the tank not being clean and dry which resulted in an attack on the loading process. This study set out to ascertain how equipment preparedness affected tank cleaning. This study employed a descriptive method with a quantitative approach as its research methodology. The IBM SPSS 26 program is used to process some sample data. Respondents are given questionnaires as part of data gathering processes.The results showed that equipment readiness had a significant effect on the tank cleaning process.